Structural Equation Modeling of Casual Factors of Effectiveness of Enrichment Program of Science, Mathematics, Technology and Environment (SMTE) of Secondary School in the Northeast Region - Bongboot, Dechathon; Peantanyakorn, Sikarn; Phothiwat, Sawat (Asia Social Issues, 2023)
The purposes of this research were 1) to study characteristics of causal factors in Structural Equation Modeling (SEM) influencing the effectiveness of science, mathematics, technology, and environment (SMTE) of Secondary Schools in the northeast region, 2) to examine the causal factors of SEM the selected developed model affecting the effectiveness of SMTE in the northeast with the empirical data, and 3) to obtain guidelines for developing the selected factors that affected the effectiveness of science, mathematics, technology, and environment special classroom project in the northeast. This study consisted of 561 related persons involved, consisting of 11 people involved in the project, 1 school director and 1 deputy director, 3 science teachers, 3 mathematics teachers and 3 teachers in computer subjects. The research methodology was conducted in 3 phases: 1) constructing the hypothesis model, 2) examination of conformance with empirical data, and 3) finding ways to develop causal factors. The tools used for the collection were a questionnaire with a five rating scale and an interview form. Statistics used for data analysis were percentage, mean, standard deviation, Pearson’s coefficient, Alpha coefficient, and the analysis of structural equation modeling. The results of the research were as follows: 1) The structural equation modeling that was created consisted of causal variables, namely school management and participation of parents and student’s physical environment in teaching and learning science and mathematics; 2) The causal factors of structural equation modeling of the project effectiveness; 3) This research presents guidelines for the development of causal factors that directly, indirectly, and overall affect the project effectiveness as follows: school management, The participation of parents and students, the physical environment and science and mathematics teaching and learning management.